2023
DOI: 10.3389/fneur.2022.1033385
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index and the incidence of stroke: A meta-analysis of cohort studies

Abstract: BackgroundInsulin resistance (IR) is involved in the pathogenesis of atherosclerosis. As a new indicator, the triglyceride-glucose (TyG) index has greater operability for the evaluation of insulin resistance. Previous studies have shown inconsistent results in evaluating the association between the TyG index and stroke incidence in people without stroke at baseline. Therefore, this study aimed to systematically assess this association through a meta-analysis.MethodsCohort studies with the multivariate-adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Our study elucidated a significant and positive association between TyG and stroke prevalence in the Chinese population, corroborating the findings of previous investigations [35,36]. However, most of the existing studies on the relationship between TyG and stroke have focused on small sample cohorts in different countries with relatively few studies conducted in large sample background [37]. Thus, our study filled this knowledge gap and enhanced the understanding of the universality of this relationship.…”
Section: Mediation Analysis Of Tyg Tyg-wc Tyg-whtr and Tyg-bmi With S...supporting
confidence: 89%
“…Our study elucidated a significant and positive association between TyG and stroke prevalence in the Chinese population, corroborating the findings of previous investigations [35,36]. However, most of the existing studies on the relationship between TyG and stroke have focused on small sample cohorts in different countries with relatively few studies conducted in large sample background [37]. Thus, our study filled this knowledge gap and enhanced the understanding of the universality of this relationship.…”
Section: Mediation Analysis Of Tyg Tyg-wc Tyg-whtr and Tyg-bmi With S...supporting
confidence: 89%
“…Despite the wealth of literature on the association between TyG index and ischemic stroke [ 39 , 40 ], atherosclerosis [ 41 ], and coronary syndromes [ 42 ], scant attention has been paid to its connection with CVDs. Our study bridges this gap by establishing a linear association between the TyG index and 28- and 90-day mortality due to CVD.…”
Section: Discussionmentioning
confidence: 99%
“…The combined variables of glucose and triglycerides make the TyG index closely associated with related metabolic diseases. Several recent studies have shown that the TyG index improves the prognosis of CVD 35 38 . Similarly, the TyG index's prognostic utility for diabetic patients has been the subject of extensive research.…”
Section: Discussionmentioning
confidence: 99%